MRP tasks, critical thinking and intrinsic motivation to proving - Takáč, Zdenko (Teaching Mathematics and Computer Science, 2010)
The lack of students’ need for proof is often discussed. This is an important topic, on which quite a few others have written ([26], [27], [28], [17], [8]). Nevertheless, there is limited research knowledge about how teacher can participate in process of raising of students’ intrinsic motivation to proving. In this article, we discuss relationships between intrinsic motivation to proving, critical thinking and special activity – engaging with so-called MRP tasks. We present here results of a research carried out by author in two elementary schools (21 classes, grade 5-9) in Ruzomberok, Slovakia. We identified the interesting relationship between students’ dealing with MRP tasks and increasing of their intrinsic motivation to proving.